2015
DOI: 10.1002/star.201500059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of process parameters and added starches on resistant starch content and sensory properties of maize extrudates

Abstract: Maize grits with or without starchy additives (native wheat starch, distarch phosphates, soluble fiber) were extruded through a single-screw laboratory extruder Brabender KE 19/25 with a controlled barrel temperature in three zones and in a head, die diameter 4 mm, comprising a compression ratio of the screw of 2:1. The purpose was to influence resistant starch (RS) content together with improving/saving key physicochemical properties by controlling extrusion cooking variables (water addition into feed of 5-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…But according to our results, the higher temperature caused a slight increase in resistant starch content (data not shown). It confi rms our previous data (ŠÁRKA et al, 2015b) that fi nal temperature is not a decisive factor for RS creation. HUTH and co-workers (2000) reported that extrusion cooking parameters and subsequent storage affected the generation of RS in extruded barley fl our.…”
Section: Effect Of Temperature Of the Headsupporting
confidence: 90%
See 1 more Smart Citation
“…But according to our results, the higher temperature caused a slight increase in resistant starch content (data not shown). It confi rms our previous data (ŠÁRKA et al, 2015b) that fi nal temperature is not a decisive factor for RS creation. HUTH and co-workers (2000) reported that extrusion cooking parameters and subsequent storage affected the generation of RS in extruded barley fl our.…”
Section: Effect Of Temperature Of the Headsupporting
confidence: 90%
“…We changed the arrangement of the device, revolutions of the screw, ratio of the added starch, temperatures of zones, etc. The design of experiments for d=4 mm was published elsewhere (ŠÁRKA et al, 2015b), where infl uence of extrusion conditions on RS content where discussed. The measured data were completed by SDS analyses and further experiments were done for d=3 mm, where better results were expected.…”
Section: Resultsmentioning
confidence: 99%
“…When ENS with a PSI of 94.1 were analyzed, the extrudates obtained at FM values of 16.5 and 20.5% had significantly higher amounts of RS. Šárka et al evaluated the effect of extrusion parameters on the resistant starch of maize extrudates. They concluded that the formation of resistant starch was related to the pressure inside the extruder.…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, the content of RS in extruded flours was also significantly reduced (ranged from 0.32 to 4.99 g/100 g) when compared with unprocessed samples (16.23 g/100 g). Low pressure in the extruder, which may be related to temperature and screw speed, also showed be a key point to maintain high resistant starch content in maize extrudates (Šárka et al, ). The retrogradation of gelatinized starch induces the reorganization of starch chains and hence the formation of resistant starch type 3 (Berry, ), which acts as a soluble fiber.…”
Section: Discussionmentioning
confidence: 99%